Penyuluhan Program Pemberian Makanan Tambahan Lokal sebagai Penanggulangan Stunting di Kota Kediri - Lintang Pertiwi; Eko Winarti (Jurnal Medika: Medika, 2024)
Stunting is a chronic nutritional problem that significantly affects children's growth and development. This community service activity aims to evaluate the impact of education on local Supplementary Feeding (PMT) in combating stunting in Kediri. The method used is education about local PMT as a measure to combat stunting. The study subjects consisted of members of Ibu Persatuan Istri Tentara (Persit) Yonif 521: Dadaha Yodha in Kediri. Data were collected through self-data questionnaires, pretests, and posttests. The results of this activity showed a significant relationship between income, health cadre status, prior knowledge about local PMT and stunting, and the level of knowledge of Ibu Persit members. Moreover, there was an increase in the Ibu Persit member’s knowledge about the role of local PMT in combating stunting and a statistically significant difference in their knowledge levels before and after the education. Education on local PMT has proven effective in enhancing Ibu Persit members' understanding of nutrition and proper dietary practices, contributing to the reduction of stunting prevalence. These findings suggest the need for the widespread implementation of local PMT education programs as a strategy to combat stunting in other areas facing similar problems.